Problem Videogame Playing Scale: A Preliminary Study of Measurement Invariance between English and Malay - Fam, Jia Yuin; Juhari, Rumaya; Madon, Zainal; Daud, Mohd Najmi (Makara Human Behavior Studies in Asia, 2025)
Purpose: Distinguishing between problematic and non-problematic gamers is a priority concern. Although the Problem Videogame Playing (PVP) Scale might be useful as a screening tool of IGD, there is little evidence to support the measurement invariance of the PVP scale. This study aimed to evaluate the psychometric properties of the English and Malay versions of the PVP scale. Methods: A total of 646 secondary school students aged between 12 and 18 years were recruited to participate in this study. Results: The unidimensional structure of the PVP scale was confirmed by confirmatory factor analysis. The PVP scale correlates well with other game-related constructs, supporting its construct validity. The internal consistency of the PVP scale is high. The configural, metric, scalar, and residual invariance models supported the English and Malay versions of the PVP scale’s measurement invariance. Conclusion: Psychometrically, the PVP scale is a reliable and valid screening tool among English-speaking and Malay-speaking samples. Extensive psychometric properties allow its use as a screening tool for IGD.